Recruitment and Selection of Human Resources within the Thecon Organization: Array - Iosif, Luminita; Grigore, Teodora (Acta Universitatis Danubius. Communicatio, 2021)
The purpose of this article is to analyze and present the mode in which the organization Thecon does the selection and recruitment of personnel. This is done through the interview method for the most part, but also trough the analysis of different recruitment announcements. Since Thecon is an organization which specializes in the IT sector, the first part of the presentation is made out of statistical data from Romania about the evolution of the IT sector, followed by the second part of the presentation that is made out of the way in which the Thecon organization attracts new talents to work inside the company.